Pengendalian Hayati Nematoda Puru Akar pada Pertanaman Jambu Biji Kristal di Lampung - I Gede Swibawa; Yuyun Fitriana; Radix Suharjo; Solikhin Solikhin; Elsa Monika; Rachmansyah A. Wardhana (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Swibawa IG, Fitriana Y, Solikhin S, Suhajo R, Monica E, Wardhana RA. 2020. Pengendalian hayati nematoda puru akar pada pertanaman jambu biji Kristal di Lampung. In: Herlinda S. et al. (Eds.) Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the main problem in guava cultivation is root knot nematodes (Meloidogyne sp.). Synthetic nematicides was not suitable for controlling of nematodes on guava because of their side effect on environment and health. Therefore, it was necessary to search the alternative control technique. This research aim was to study the Purpureocillium lilacinum bionematicide to control root knot nematode on Kristal guava plantation. Field experiment with Block Experimental Design with five block was conducted in Kristal guava plantation belonging PT GGP-PG4 East Lampung, from January until May 2020. Four treatment were applied consisted of bionematicide, bionematicide plus compost, synthetic Carbofuran nematicide, and check without treatment. New shoot formation data were plotted on histogram graph, while analyses of variance was applied for root damage and nematode population and LSD test was used for mean separation by R-studio program on 5% significance level. The results show that application of P. lilacinum bionematicide solely or composed with compost were effective to control root knot nematodes on Kristal guava plantation. It was recommended to use bionematicides P. lilacinum plus compost to control plant parasitic nematodes for various cultivated plants.